Hubungan Kecepatan Terhadap Ketrampilan Menggiring Bola Dalam Sepak Bola Pada Siswa Kelas VIII SMP Negeri 7 Dumoga - Yosua Tumbel; Marnex W. Berhimpong; Maxi M. L Moleong (STIKES Columbia Asia Medan, 2025)
This study aims to analyze the relationship between speed and dribbling skills in eighth grade students. Dribbling skills are one of the basic skills in football that are important for the effectiveness of the game. Speed ​​in dribbling the ball plays a key role in improving an individual's ability to face opponents and carry out effective attacks. The research approach used is quantitative with a correlational method. The population in this study were all eighth grade students at SMP Negeri 7 Dumoga, with samples selected randomly. The research instruments included a speed test and a dribbling skills test, each of which was measured through a standardized trial. The results showed that there was a significant negative relationship between speed and dribbling skills with a Pearson correlation value of -0.65 and a significance of 0.001. This indicates that students who have higher speed tend to have better dribbling skills. This finding is consistent with previous studies stating that speed is an important factor in the development of dribbling skills. Based on the results of the study, it is recommended that coaches and sports teachers focus more on speed training in soccer training programs to improve students' dribbling skills.